Streptococcus abundance and oral site tropism in humans and non-human primates reflects host and lifestyle differences - Irina M. Velsko; Christina Warinner (npj Biofilms and Microbiomes)
Abstract The genus Streptococcus is highly diverse and a core member of the primate oral microbiome. Streptococcus species are grouped into at least eight phylogenetically-supported clades, five of which are found almost exclusively in the oral cavity. We explored the dominant Streptococcus phylogenetic clades in samples from multiple oral sites and from ancient and modern-day humans and non-human primates and found that clade dominance is conserved across human oral sites, with most Streptococcus reads assigned to species falling in the Sanguinis or Mitis clades. However, minor differences in the presence and abundance of individual species within each clade differentiated human lifestyles, with loss of S. sinensis appearing to correlate with toothbrushing. Of the non-human primates, only baboons show clade abundance patterns similar to humans, suggesting that a habitat and diet similar to that of early humans may favor the growth of Sanguinis and Mitis clade species.